Medicated Lozenges: A Review: Artificial intelligence in drug discovery - Gopale, Onkar; Jethawa, Shraddha; Shelke, Suvarna (Asian Journal of Pharmaceutical Research and Development, 2022)
A lozenge is a solid dose form of a medicine that is meant to dissolve in the mouth or throat. The creation of lozenges began in the 20th century and is continuing in use now. The advantages of lozenges include an increase in the duration of oral form retention in the oral cavity, which is beneficial. Bioavailability is improved. The difference lowers stomach distress and bypasses the first pass metabolism. Compressed lozenges , hard and soft lozenges are a form of lozenge that is available on the market.n this review there is a method of preparation of lozenges with materials that is required for lozenges are addressed. This review also include the research to date, classification, advantages, disadvantages, formulation evaluation, packaging, storage, uses and parameters of the study